1973
DOI: 10.1021/ja00805a029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of oxidative cyclization of squalene. Evidence for cyclization of squalene from either end of the squalene molecule in the in vivo biosynthesis of fusidic acid by Fusidium coccineum

Abstract: phenyl phosphide was prepared by the reaction of diphenylphosphine with n-butyllithium in THF. Lithium diphenylamide was prepared by the reaction of diphenylamine with methyllithium in THF. Sodium dimsylate was prepared as described by Greenwald, Chaykovsky, and Corey.80 All of the above were reacted with carbon monoxide at 200 psi; only sodium dimsylate took up an appreciable quantity of carbon monoxide (0.5 equiv of carbon monoxide per equivalent of dimsylate over a 24-hr period). Dilithium Benzophenone Dian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1974
1974
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…By examining the distribution of in lanosterol synthesized from farnesyl pyrophosphate in the presence of NADP3H, Etemadi et al (1969) concluded that the biosynthesized squalene had randomized. Ebersole et al (1973) incubated (3i? )-[2-14C]-( 55)-[5-3H]mevalonate with cultures of Fusidium coccineum.…”
Section: Discussionmentioning
confidence: 99%
“…By examining the distribution of in lanosterol synthesized from farnesyl pyrophosphate in the presence of NADP3H, Etemadi et al (1969) concluded that the biosynthesized squalene had randomized. Ebersole et al (1973) incubated (3i? )-[2-14C]-( 55)-[5-3H]mevalonate with cultures of Fusidium coccineum.…”
Section: Discussionmentioning
confidence: 99%
“…Zhankuic acid B (2, 20 mg) was obtained from fraction 4 by prep, tic (Si gel, toluene-EtOAc-HOAc, 10:1:0.5). Zhankuic acid C (3, 300 mg) was obtained directly from the recrystallization of fraction 1 and 2; hreims mlz 468.2872 (C29H40O3, caled 468.2876); eims mlz 468 (M+, 56), 450 (9), 424 (78), 354 (64), 339 (33), 326 (22), 313 (18), 311 (63), 297 (11), 286 (42), 271 (22), 260 (30), 246 (10), 231 (8), 220 (23), 215 (7), 201 (6), 189 (8), 175 (9), 161 (9), 149 (9), 135 (14), 123 (20), 121 (17) 109 (38), 95 (100), 82 (13), 68 (30). Zhankuic acid A methyl ester [4],-A solution of 1(100 mg) was treated overnight with an excess amount of CH2N2 in Et20.…”
mentioning
confidence: 99%
“…Elimination of a proton would result in dehydrogammacerane (17b). Alternatively, 15 could rearrange to the hopanoidyl cation 13b which in turn could be stabilized in a number of ways. For example, loss of a proton would result in hop-22-ene (18), while acquisition of a hydroxyl would yield diplopterol (26).…”
mentioning
confidence: 99%